Evaluasi Sistem Dapodikmen Dengan Pendekatan Utility System Pada Sekolah Menengah Atas Negeri Kota Palembang - Raden Ayu Indriansari; Darius Antoni; Linda Atika (Jurnal Nasional Ilmu Komputer, 2020)
Dapodikmen system has not yet reached its accurately and effective utilization.. The results of observation and interview done to school operators in some high schools in Palembang show that there are different factors which determine the effectiveness of the system, for example, the content of information, ease of access and availability of the system which often has not been in accordance with the users’ needs. One approach used to evaluate the effectiveness of the system is the System Utility. The approach by Kendall & Kendall, 2007 (in Martoyo, 2015:638) review the success of the system implementation from six points of view, namely possession, goal, place, form, time and actualization utility. This approach is included in the category of system effectiveness evaluation viewed from the user's expectations. The results of this study demonstrate that of the aspect of variable utility and value of the Dapodikmen system is 4, 2636. This concludes that the availability of the system in high schools in Palembang city is effective.